ANALISIS PENGGUNAAN APLIKASI SISTEM INFORMASI LOGISTIK (SIL) UNTUK PERENCANAAN, PELAPORAN DAN PENGENDALIAN BERBASIS WEB DAN PENGARUHNYA TERHADAP KINERJA DAN KEPUASAN PENGGUNA (Studi pada : Pengguna Aplikasi SIL Perum Bulog Divisi Regional Jawa Timur) - Fazizah, Amma; Sukoharsono, Eko Ganis; Kertahadi, Kertahadi (Profit: Jurnal Adminsitrasi Bisnis, 2016)
Use of computer technology properly and optimally utilized by the BULOG Public Company. Perum Bulog utilizing information and communication technology to provide information related to inventory logistics and other operational activities. This study aimed to analyze the use of SIL applications for planning (X1), the use of SIL applications for reporting (X2) use SIL applications for logistics control (X3) and its effect on performance (Y1) and User Experience (Y2). The study is an explanatory reseach with survey approach. The object of the study is an user SIL applications. This study took place in Perum Bulog East Java Regional Division A. Yani 146-148 Jalan Surabaya. The sample are of to 88 users. Instruments in this study using a questionnaire with data analysis method using path analysis. Tools or software used in statistical data processing research was SPSS 20. Â Based on the results of the study, data analysis, and discussion of the results of study and testing hypotheses 7 are performed, there are six hypotheses were significant accepted, and the first hypothesis is rejected. Accepted hypothesis H1 include the use of SIL applications for logistics planning has significant positive effect on user performance, H2 using a SIL applications for logistics planning significant positive effect on user satisfaction, H3 using a SIL applications for logistics reporting has significant positive effect on user performance, H4 using a SIL applications for logistics planning no significant effect on user satisfaction, H5 using a SIL applications for logistics control has significant positive effect on user performance, H6 using a SIL applications for logistics control has significant positive effect on user satisfaction and user performance H7 significant positive effect on user satisfaction.Â Â